Strategic Integration of Sustainability, Circular Economy, and Blockchain in Slovenian Urban Governance - Justinek, Gorazd (LeXonomica, 2025)
Slovenia has 12 urban municipalities, each with a sustainable development strategy aligned with the Agenda 2030 framework and valid through 2030. This paper examines how these strategies incorporate emerging technologies, particularly blockchain, and innovative sustainability concepts such as the circular economy. Achieving the goals of Agenda 2030, especially transitioning to a circular economy, requires doubling energy efficiency by 2030. While blockchain and the circular economy have often been studied separately, this research explores their intersection within the context of urban sustainability. The study applies qualitative content analysis to the official development strategies of all 12 urban municipalities. This analysis is complemented by semi-structured interviews with senior officials from the Ministry of the Environment, Climate and Energy, and the Vice Mayor of Ljubljana, providing institutional perspectives on strategic priorities and implementation logic. This is the first comprehensive analysis of how Slovenian urban municipalities address the interconnected themes of sustainability, circular economy, and blockchain technology. The findings contribute to academic discussions and offer practical recommendations to enhance innovation in urban sustainability planning.Povzetek članka v slovenskem jeziku (abstract in Slovene language):Slovenija ima 12 mestnih občin, vsaka z lastno strategijo trajnostnega razvoja, ki je usklajena z okvirom Agende 2030. Prispevek preučuje, kako te strategije vključujejo nove tehnologije, zlasti tehnologijo veriženja blokov (blockchain), ter inovativne trajnostne koncepte, kot je krožno gospodarstvo. Za dosego ciljev Agende 2030, predvsem pri prehodu na krožno gospodarstvo, je treba do leta 2030 podvojiti energetsko učinkovitost. Medtem ko sta blockchain in krožno gospodarstvo pogosto raziskana ločeno, ta raziskava proučuje njuno presečišče v kontekstu trajnosti mest. Študija uporablja kvalitativno analizo vsebine uradnih razvojnih strategij vseh 12 mestnih občin. Analizo dopolnjujejo polstrukturirani intervjuji z visokimi uradniki Ministrstva za okolje, podnebje in energijo ter s podžupanom Mestne občine Ljubljana, ki podajo institucionalne poglede na strateške prioritete. To je prva celovita analiza, kako slovenske mestne občine obravnavajo medsebojno povezane teme trajnosti, krožnega gospodarstva in tehnologije veriženja blokov. Ugotovitve prispevajo k akademskim razpravam in ponujajo praktična priporočila za krepitev inovativnosti pri načrtovanju trajnostnega razvoja mest.